Recurrent Volvulus of an Ileal Pouch Requiring Repeat Pouchopexy: A Lesson Learnt - Pär Myrelid; Pelle Druvefors; Peter Andersson (Case Reports in Surgery)
Introduction. Restorative surgery for ulcerative colitis with ileal pouch anal anastomosis (IPAA) is frequently accompanied by complications. Volvulus of the ileal pouch is one of the most rarely reported late complications and to our knowledge no report exists on reoperative surgery for this condition. Case Report. A 58-year-old woman who previously had undergone restorative proctocolectomy due to ulcerative colitis with an IPAA presented with volvulus of the pouch. She was operated with a single row pouchopexy to the presacral fascia. Two months later she returned with a recurrent volvulus. At reoperation, the pouch was found to have become completely detached from the fascia. A new pexy was made by firmly anchoring the pouch with two rows of sutures to the presacral fascia as well as with sutures to the lateral pelvic walls. At follow-up after five months she was free of symptoms. Conclusion. This first report ever on reoperative surgery for volvulus of a pelvic pouch indicates that a single row pouchopexy might be insufficient for preventing retwisting. Several rows seem to be needed.